Quantitative Structure-Activity Relationship Studies of Bifendate Derivatives - WEI, QING-LI; GAO, JUN; ZHANG, SHU-SHENG; LIU, NIAN (Asian Journal of Chemistry, 2010)
The quantitative structure-activity relationship (QSAR) of bifendate derivatives was investigated by molecular dynamics and quantum chemical ab initio method, and EHOMO, ELUMO, Φ and the population of atom charges were calculated. The quantitative relationship between activity of the compounds and EHOMO, logP and Φ was analyzed by using the stepwise multiple regression based on Hansch-Fujita approach. A correlative equation was well established. The multiple correlation coefficient r is 0.6664 and the test-value of F is 3.46085.